The Implementation Of Benson Relaxation To The Reduction Of Blood Pressure In Patients With Emergency Hypertension Activities In dr R. Soeprapto Cepu Emergency Departments - Mu'awanah Mu'awanah; Sri Hastuti; M. Nor Mudhofar; Heru Purnomo; Siti Solichah (Jurnal Studi Keperawatan, 2022)
Background: Hypertension emergency is characterized by an increase in blood pressure 180/120 mmHg accompanied by evidence of new or worsening target organ damage. A drop in blood pressure within minutes or hours must be done immediately to prevent complications. Nursing action that can be used to lower blood pressure is Benson relaxation. When a state of relaxation occurs there is a decrease in emotional arousal and a decrease in excitability in areas that regulate cardiovascular function which will reduce blood pressure.Formulation of the problem: Benson's relaxation action has not been carried out by the emergency room nurse at RSUD DR R Soeprapto Cepu in the handling of emergency hypertension patientsPurpose: The aim of this scientific paper is to determine whether there is an effect of giving Benson relaxation therapy to lower blood pressure in patients with hypertensive emergency.Methods: The method used in the preparation of this research uses a journal search with Google scholar, Science direct and Pubmed.Results: There is a significant effect of Benson relaxation on blood pressure reduction and it can be used as a non-pharmacological treatment in lowering blood pressure.Conclusion: It can be used as a reference for optimizing the provision of Benson relaxation therapy in hypertensive emergency patients to accelerate the decrease in blood pressure. Keyword : benson; hypertension; blood pressure